Captive breeding of mud crab Scylla serrata (Forskål, 1975) in Bangladesh - Hoq, Md Enamul; Sein, Aung; Khan, Md Shahzad Kuli; Debnath, Partho Pratim; Kudrat E Kabir, Quazi AZM (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 42(2): 295-299, 2014